Mesoporous SnO2 Nanowires: Synthesis and Ethanol Sensing Properties - Shan-Hong Li; Fang-Fang Meng; Zhong Chu; Tao Luo; Fu-Min Peng; Zhen Jin (Advances in Condensed Matter Physics)
The mesoporous SnO2 nanowires composed of nanoparticles and nanopores have been successfully synthesized within the nanochannels of anodic alumina oxide templates by a facile sol-gel method. XRD, SEM, and HRTEM were used to characterize the synthesized mesoporous SnO2 nanowires. The sensing property of the mesoporous SnO2 nanowires in ethanol detection also has been studied. The as-prepared product displays excellent the high sensitivity, rapid response, and excellent repeatability to ethanol. The detection limit of the mesoporous SnO2 nanowires to ethanol reaches 1 ppm. The sensing mechanism of the mesoporous SnO2 nanowires has been further discussed. It is expected that the mesoporous SnO2 nanowires might become a good sensing material for promising industrial applications.